Image Smoothing Pada Citra Ultrasonografi (USG) Dengan Metode Harmonic Mean Filter - Liyanti Armaya Sari; Yani Maulita; Indah Ambarita (UIN Sumatera Utara, 2021)
Technological developments have changed computers so that they can process various kinds of data such as sound, images, and so on. All of these data can only be processed if the data has become data in digital form. The sophistication of computer technology that is growing rapidly can also be used to simplify and save costs. One of the uses of technological developments is the Ultrasonography (USG) process in the health sector. Medical ultrasound (USG) is a diagnostic imaging technique using ultrasound that is used to image internal organs and muscles, their size, structure, and pathological wounds, making this technique useful for examining organs. The problem that often occurs in printed ultrasound images is that they experience blurring due to the presence of a lot of noise in the image. Noise is caused by the imperfect wave capture process, so the resulting image is not optimal. One method in the image smoothing process is the Harmonic Mean Filter method which is a filtering technique that works by replacing the intensity of a pixel with the average pixel value of the neighboring pixels with the aim of reducing noise in the image. Pixels resulting from the image smoothing process are affected by the neighboring pixel values. The system is designed with the MATLAB R2014a programming application, after carrying out the testing process on several Ultrasonography (USG) images, the results show that the average percentage of the image improvement process is above 50% and the smoothing ultrasound image on the system is better than the image inputted to the system. Keywords: Harmonic_Mean_Filter, Image_Smoothing, Ultrasonography.